Environmental innovations in industry - Sayenko, V. (Харківський національний автомобільно-дорожній університет, 2023)
Object research - processes formation structures and properties teeth buckets excavators ion-plasma chroming. Property from ub iv buckets excavators changed applying ion-plasma coatings chromium nitride. This species is selected for protection from corrosion, wear, sticking to the surface contacts mater ials. In practice modern enterprises are applied causing chrome coatings to increase the service life teeth buckets excavators. Quality these coverage in does not meet the needs of modern production. There are many nowadays attention is provided application modern methods superficial processing for increasing wear resistance of parts of nodes that work in the conditions intensive wear and tear. Based on analysis literary data and experience modern we had enterprises - the ion-plasma method is chosen processing teeth buckets excavators, for increase their longevity. Causing coatings was carried out by the method of condensation in the conditions ionic bombing of the Bulat 3T installation. Was selected coating composition and optimal modes him causing. Received high hardness and wear resistance, low coefficient friction, good chemical stability what provided a high resource of researched details in any conditions operation.
Екологічні інновації в промисловості
Keywords: wear resistance; abrasive; welding; plasma; ladle; layer; corrosion; steel.; 621.878